Absorption and metabolites of anthocyanins and phenolic acids after consumption of purple wheat crackers and bars by healthy adults. (March 2019) - Gamel, Tamer H.; Wright, Amanda J.; Tucker, Amy J.; Pickard, Mark; Rabalski, Iwona; Podgorski, Margaret; Di Ilio, Nicholas; O'Brien, Charlene; Abdel-Aal, El-Sayed M.
Abstract: The physiological effects of polyphenols in human health are dependent on their bioavailability and metabolism. The aim of this study was to determine anthocyanin and phenolic acid metabolites and their absorption following acute consumption of two purple wheat products by healthy adults. A secondary objective was to track changes in plasma antioxidant status and short-term markers of inflammation postprandially for 8 h. Anthocyanin and phenolic acid metabolites were quantified in the plasma and urine of 16 healthy female and male participants following the consumption of 4 servings of bran-enriched purple wheat bars and crackers containing 6.7 mg anthocyanins and 176–213 mg total phenolic acids. A few anthocyanin metabolites were detected in the urine and none were found in plasma. Ferulic acid was detected in plasma and urine, while hippuric acid was the major metabolite in the urine. The maximum plasma concentration of ferulic acid and phenolic acid metabolites reached 9–31 and 765-745 ng/mL within 30–60 min following products consumption. With acute consumption of purple wheat bars and crackers by healthy adults, rapid absorption and excretion of anthocyanin and phenolic acid metabolites was observed with no short-term impacts on plasma antioxidant activity or the inflammatory biomarkers, IL-6 and TNF-α. Highlights: Purple wheat products are rich in anthocyanins and phenolic acids. Ferulic acid is the principal polyphenol/metabolite found in plasma and urine. Little changes found in plasma antioxidant status during 8 h of product consumption. Slight changes occurred in inflammation markers during 8 h of product consumption.